Assessing Equity in Protected Area Governance: Approaches to Promote Just and Effective Conservation. Issue 2 (5th July 2017) - Dawson, Neil; Martin, Adrian; Danielsen, Finn
Abstract: With the inclusion of equity concerns in Aichi Target 11 of the Convention on Biological Diversity, equitable management has become an important objective for the world's protected areas. The way equity is defined and operationalized influences whether this strategic shift can help identify pathways commensurate with conservation effectiveness. We examined equity around a protected area in Laos, combining quantitative and qualitative methods to explore the three dimensions of procedure, recognition, and distribution. Local understandings of equity depended on discrete, evolving issues, with attention to informal decision making and dynamic values required to uncover suitable solutions. We show that equity definitions focused on material distribution and assessments reliant on standardized indicators may result in inadequate responses that sustain local perceptions of inequitable management and miss opportunities for effective conservation. Equity should be considered a management goal to continually adapt toward, informed by stakeholder dialogue.